USING INFORMATION GAP ACTIVITIES - Karshi SU; Turayeva G.X. (Western European Studies, 2024)
The type of classroom activities proposed in CLT also impliednew roles in the classroom for teachers and learners. Speaking is a fundamental language skill. It is the primary way in which we communicate information. Information gap activity is the way of encouraging speaking ability and speaking refers to the gap between linguistic expertise and teaching methods.
Keywords: communicative; competence; communication